PERBANDINGAN HASIL TANGKAPAN UTAMA DAN SAMPINGAN ALAT TANGKAP TRAWL PADA MALAM HARI DI PERAIRAN SAMBOJA KUALA KABUPATEN KUTAI KARTANEGARA - Ahmad Fauzi; Muhammad R. Syahrir; Nurfadilah Nurfadilah (Jurnal Tropical Aquatic Sciences, 2022)
As an area bordering the Makassar Strait, Samboja Kuala District, most of the people make a living as fishermen. The fishing gear used by fishermen to catch shrimp and fish is a trawl. This study aims to identify the types of catches, determine the comparison of the percentage of main and by-catch at night. The method used in this study is a survey method, namely by going directly to the field. The main catches were 8 species of shrimp, namely Penaeus monodon, Penaeus sp, Penaeus merguiensis, Metapenaus affinis, Metapenaus monoceros, Metapenaeopsis palmenis, Metapenaeopsis barbata and Solenocera crassicornis. While the by-catch there are species of fish, cuttlefish and squid. The percentage of the main catch that was dominantly caught was Metapenaus affinis at 61% and the smallest was Penaeus sp 0%. While the percentage of by-catch is the most dominant fish beloso 33% and the smallest is grouper and bigeye fish 1% with a significance value <0.05 (sig. 0.24). The results of this study can show that there are differences in the main catch and by-catch in trawl fishing gear at night.